Future Impact on Pakistan Economy in the 21st Century Shifting of Global Power - Muhammad Ismail; Rani Siti Fitriani (Universitas Kristen Indonesia Toraja, 2022)
The Wakhan Corridor is surrounded by the concerned region of Mekandar. The access strip is located at the intersection of four countries, the mainland of Afghanistan, Tajikistan, China and Pakistan. The Wakhan Corridor has been the mainly vital intersection point of the Silk Road since its inception. This corridor has long been used by Europeans and Chinese as a trade path to reach the Indian plains and sea lines of communication in the Indian Ocean via the coasts of the Arabian Sea. At the joint of China, Pakistan, Afghanistan and Tajikistan lies a small extend of land in Afghanistan's Badakhshan province known as the Wakhan Corridor. Being a passage of the old Silk Road, this corridor is of great historical value. It still has a lot of room for increase in terms of tourism and regional connectivity. Wakhan region is considered relatively peaceful as there is no law-and-order problem. Construction of the road through Wakhan will improve regional trade and business, especially for Pakistan, Central Asia and Afghanistan. It could provide the fastest trade route for China to access Afghanistan and Pakistan for access to Central Asia. In this context, the research explores the possibilities of revitalizing the Wakhan Corridor through the construction of road infrastructure. This paper highlights the economical importance of the Wakhan Corridor in the light of the emerging regional scenario. Both ISIS and the Pakistani Taliban are essential to disrupt the corridor and create security challenges for development. To benefit from future trade improvements along the Wakhan Corridor, the three countries (Pakistan, China and Tajikistan) should focus on the security and political situation.